WHAT INFLUENCES UNEMPLOYMENT IN ACEH PROVINCE - Mahrizal, Mahrizal; Maidiansyah, Putra (Jurnal Ilmiah Teunuleh, 2022)
Indonesia is one of the countries with the largest population in the world and is a big capital for Indonesia in development. A large population if not managed properly will cause unemployment problems. The most remote province of Sumatra, namely the province of Aceh, is one of the provinces that has a high open unemployment rate. Thus, it is necessary to analyze the factors that influence the open unemployment rate. This study aims to analyze the effect of the provincial minimum wage, economic growth and inflation on the open unemployment rate in Aceh Barat district. The type of research used is quantitative research using multiple linear regression method with time series data (time series) for 2012-2021, namely 10 years including provincial minimum wage data, economic growth data, inflation data, open unemployment rate data, and processed using the SPSS program. 25. The results of this study indicate that simultaneously the F test of the provincial minimum wage, economic growth and inflation together affects the level of open unemployment in Aceh Barat district. While partially, namely the t test, it is concluded that the provincial minimum wage has a positive and significant effect on the level of open unemployment, economic growth has a negative and significant effect on the unemployment rate and inflation has a negative and significant effect on the open unemployment rate in Aceh Barat district.